Historical Synopsis of Nifāq (Hypocrisy) and Prophetic Response in Madinah - Ammaru Ummaru; Setiawan, Agus Mahfudin (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2025)
Abstract: This historical study investigates the emergence and dynamics of hypocrisy (nifāq) in the early Islamic community of Madinah and explores the strategic responses of Prophet Muḥammad (SAW) in mitigating internal threats posed by the Munāfiqūn (hypocrites). Using a historical-analytical method, the research draws upon primary sources such as the Qur’an, ḥadīth, classical sīrah, and early Islamic historiography, while contextualizing the findings with modern scholarly insights. The study identifies a series of conspiratorial acts orchestrated by ‘Abdullāh b. Ubayy and his followers—ranging from military desertion, rumor-spreading, alliance with enemies, to attempts at division through rival institutions. The analysis demonstrates that the Prophet’s (SAW) leadership was historically grounded in restraint, long-term vision, and political maturity, prioritizing social cohesion over immediate retribution. By interpreting these responses as part of a conscious historical strategy, the research highlights the relevance of the Prophetic model in contemporary Muslim leadership, especially in managing intra-community tensions and ideological fragmentation. This paper contributes to Islamic historical scholarship by revisiting early Madinan society through the lens of conflict and governance and proposes further interdisciplinary research that bridges prophetic leadership with historical and political thought in Islamic civilization. Abstrak: Studi sejarah ini menyelidiki kemunculan dan dinamika kemunafikan (nifāq) dalam komunitas Islam awal Madinah dan mengeksplorasi tanggapan strategis Nabi Muhammad (SAW) dalam mengurangi ancaman internal yang ditimbulkan oleh Munāfiqūn (munafik). mengunakan metode historis-analitis, penelitian ini mengacu pada sumber-sumber primer seperti Al-Qur'an, ḥadīth, sīrah klasik, dan historiografi Islam awal, sambil mengkontekstualisasikan temuan dengan wawasan ilmiah modern. Studi ini mengidentifikasi serangkaian tindakan konspirasi yang diatur oleh 'Abdullāh b. Ubayy dan para pengikutnya—mulai dari desersi militer, penyebaran rumor, aliansi dengan musuh, hingga upaya perpecahan melalui lembaga saingan. Analisis menunjukkan bahwa kepemimpinan Nabi (SAW) secara historis didasarkan pada pengekangan, visi jangka panjang, dan kematangan politik, memprioritaskan kohesi sosial daripada pembalasan segera. Dengan menafsirkan tanggapan ini sebagai bagian dari strategi sejarah yang sadar, penelitian ini menyoroti relevansi model Profetik dalam kepemimpinan Muslim kontemporer, terutama dalam mengelola ketegangan intra-komunitas dan fragmentasi ideologis. Makalah ini berkontribusi pada keilmuan sejarah Islam dengan meninjau kembali masyarakat Madinan awal melalui lensa konflik dan pemerintahan, dan mengusulkan penelitian interdisipliner lebih lanjut yang menjembatani kepemimpinan profetik dengan pemikiran sejarah dan politik dalam peradaban Islam.